Warm springs, early lay dates, and double brooding in a North American migratory songbird, the black-throated blue warbler. - Andrea K Townsend (Public Library of Science (PLoS), 2013)
Numerous studies have correlated the advancement of lay date in birds with warming climate trends, yet the fitness effects associated with this phenological response have been examined in only a small number of species. Most of these species--primarily insectivorous cavity nesters in Europe--exhibit fitness declines associated with increasing asynchrony with prey. Here, we use 25 years of demographic data, collected from 1986 to 2010, to examine the effects of spring temperature on breeding initiation date, double brooding, and annual fecundity in a Nearctic-Neotropical migratory songbird, the black-throated blue warbler (Setophaga caerulescens). Data were collected from birds breeding at the Hubbard Brook Experimental Forest, New Hampshire, USA, where long-term trends toward warmer springs have been recorded. We found that black-throated blue warblers initiated breeding earlier in warmer springs, that early breeders were more likely to attempt a second brood than those starting later in the season, and that double brooding and lay date were linked to higher annual fecundity. Accordingly, we found selection favored earlier breeding in most years. However, in contrast to studies of several other long-distance migratory species in Europe, this selection pressure was not stronger in warmer springs, indicating that these warblers were able to adjust mean lay date appropriately to substantial inter-annual variation in spring temperature. Our results suggest that this North American migratory songbird might not experience the same fecundity declines as songbirds that are unable to adjust their timing of breeding in pace with spring temperatures.